Spatial dependence of soil attributes in natural field and forest areas, Humaitá, AM - Lourenço, Igor Hister; Campos, Milton Cesar Costa; Alho, Leandro Coutinho; da Cunha, José Maurício; Mantovaneli, Bruno; da Silva, Douglas Marcelo Pinheiro (Acta Iguazu, 2019)
The great geological diversity in Amazonas region generates a variety of soils. Among the various vegetation types in the Amazon, we have in the Southern region, toposequences of natural fields and forests, which includes since grasslands with alternated small trees, to isolated forest galleries along streams. The aim of this study was to use scaled semivariograms in spatial dependence of soil attributes in areas of natural fields and forest in Humaitá, AM region. Sampling networks were established with 64 points, with dimensions of 70 x 70 m and regular spacing of 10 m. The soil was sampled at depths of 0 – 0.05; 0.05 – 0.10 and 0.10 – 0.20 m for the following determinations: macroporosity, microporosity, total porosity, soil moisture, soil resistance penetration (SRP), bulk density, organic carbon, storage carbon and soil organic matter. All variables showed a strong spatial dependence structure in both areas and layers, reaching upper ranges than those established in the mesh. Bulk density (BD) and soil resistance penetration (SRP) in natural field area, can yet cause agricultural problems.